Source and reduction of nitrous oxide - Pauleta, Sofia R. (2022)
PTDC/BBB-BQB/0129/2014. UID/QUI/50006/2019. UlD/Multi/04378/2019. MSPC acknowledges FCT/MCTES for funding her "Research Position" (signed with FCT NOVA in accordance with DL.57/2016 and Lei 57/2017). Sem PDF conforme despacho.